2016
DOI: 10.1038/srep38124
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone status defines brown adipose tissue activity and browning of white adipose tissues in mice

Abstract: The present study aimed to determine the effect of thyroid hormone dysfunction on brown adipose tissue activity and white adipose tissue browning in mice. Twenty randomized female C57BL/6NTac mice per treatment group housed at room temperature were rendered hypothyroid or hyperthyroid. In-vivo small animal 18F-FDG PET/MRI was performed to determine the effects of hypo- and hyperthyroidism on BAT mass and BAT activity. Ex-vivo14C-acetate loading assay and assessment of thermogenic gene and protein expression pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 51 publications
7
70
2
3
Order By: Relevance
“…Together these studies indicate an important role for TH regulation of WAT thermogenesis during cold exposure. However, another recent study paradoxically showed that both hyperthyroidism and hypothyroidism increased WAT browning in mice [38]. Since the hypothyroid mice showed reduced BAT activity, the authors hypothesized compensatory WAT browning in response to decreased heat production due to BAT inactivity, as suggested previously by others [39].…”
Section: Effects Of Th On Adaptive Thermogenesis and Heat Conservationsupporting
confidence: 49%
“…Together these studies indicate an important role for TH regulation of WAT thermogenesis during cold exposure. However, another recent study paradoxically showed that both hyperthyroidism and hypothyroidism increased WAT browning in mice [38]. Since the hypothyroid mice showed reduced BAT activity, the authors hypothesized compensatory WAT browning in response to decreased heat production due to BAT inactivity, as suggested previously by others [39].…”
Section: Effects Of Th On Adaptive Thermogenesis and Heat Conservationsupporting
confidence: 49%
“…Fixed ganglia were washed in tris-PBS (TPBS) to remove fixative before being incubated in increasing concentrations of a fructose solution (20,40,60,80, and 100%) containing 0.5% a-thioglycerol for 6 h each. The tissues were then transferred, stored, and imaged in SeeDB solution [80.2 (w/w) fructose solution+0.5% a-thioglycerol].…”
Section: Determination Of the Total Number Of Prv Labeled Neurons In mentioning
confidence: 99%
“…Primarily by hepatic action, thyroid hormone therapy can lower the circulating concentration of cholesterol and lipoproteins (Angelin and Rudling, 2010). In adipose depots, thyroid hormone can promote energy expenditure and lipolysis (Lin et al, 2015;Weiner et al, 2016). Central actions of thyroid hormone include hyperphagia and sympathetic outflow, which can also increase energy expenditure and cardiovascular adrenergic input (Lopez et al, 2010;Mittag et al, 2013).…”
Section: B Glucagon-mediated Delivery Of Thyroid Hormone Tri-iodothymentioning
confidence: 99%